Cultural minority students' experiences with intercultural competency in medical education. Issue 5 (May 2017) - Leyerzapf, Hannah; Abma, Tineke
Abstract : Context: Medical schools increasingly value and focus on teaching students intercultural competency within present‐day multicultural society. Little is known about the experiences of cultural minority students in intercultural competence activities. Objectives: This article discusses the intercultural competence activities of medical education in a Dutch university from the perspective of cultural minority students. We will formulate recommendations for how to stimulate intercultural competency in, as well as inclusiveness of, medical education. Methods: A qualitative evaluation was performed within a medical school in the Netherlands. Data were collected through interviews ( n  = 23), a focus group (six participants) and participant observations (20 hours). Thematic analysis was performed. Results: Cultural minority students experienced a lack of respect and understanding by cultural majority students and teachers. Education activities intended to transfer intercultural knowledge, address personal prejudice and stimulate intercultural sensitivity were perceived as stigmatising and as creating an unsafe climate for cultural minority students. Cultural minority and majority students on campus seemed segregated and the intercultural awareness of minority students was not integrated in intercultural competence activities. Conclusions: As cultural minority students were confronted with microaggressions, the medical school did not succeed in creating a safe education environment for all students. Contrary to their aims and intentions, intercultural competence activities had limited effect and seemed to support the polarisation of cultural minority and majority students and teachers. This can be seen as pointing towards a hidden curriculum privileging majority over minority students. For structural integration of intercultural competency in medical education, the focus must penetrate beyond curricular activities towards the critical addressing of the culture and structure of medical school. Collective commitment to creating a safe and inclusive education climate is vital. This requires fostering social cohesion between minority and majority students and teachers, raising awareness and the practice by all involved of critical (self‐)reflexivity on cultural prejudice and dominant, exclusionary norms in academic medicine.